DETECTION OF CIRCULATING AUTOANTIBODIES TO HA-RECEPTORS IN HUMAN LUNG CANCER - VENKATRAO. NUNNA; BANERJEE. SD; KARUNA KUMAR. M (International Journal of Pharma and Bio Sciences, 2014)
Identification of circulating autoantibodies to hyaluronan-receptors in lung cancer holds great promise and these HA-receptors might be a potential biomarker, but remains technically challenging. Interaction and involvement of hyaluronan with specific cell surface receptors such as CD44, RHAMM and with intracellular HABP in modulating cellular behavior has been predicted. In the present study, we detected autoantibodies and their corresponding antigens (HA-receptors) by immunoblotting and sensitive ELISA. Identified antigens (HA-receptors by immunoaffinity purified autoantibody IgM) whether have binding motifs to HA or not, were further confirmed by competition experiments. HA abolish 91% binding of autoantibodies to it’s receptors. These results implicate that autoantibody IgM reacting proteins might be a HABPs. In conclusion, identification of circulating tumor antigens (HA-receptors) or their related autoantibodies provide a means for early detection and diagnosis of cancer.